PTU-051 Post-Partum Defecatory Dysfunction: A Complex Problem Involving Co-Existing Faecal Incontinence and Rectal Evacuatory Disorder. (4th June 2013) - Horrocks, E; Jordan, P; Burgell, R; Scott, M; Knowles, C
Abstract : Introduction: Faecal incontinence and urgency are well-recognised sequelae of obstetric injury, however there is a paucity of literature describing the co-existence of symptoms of rectal evacuatory dysfunction (RED) and faecal incontinence (FI). This study aims to analyse and quantify these symptoms in patients referred for anorectal investigations following obstetric injury. Methods: Consecutive patients undergoing specialist investigation at a tertiary referral unit following obstetric injury between 1st July 2010 and 31st July 2012 were identified. Symptoms at presentation were ascertained from the history. Patients routinely complete a Cleveland Clinic Constipation Score (CCCS) and Vaizey Incontinence score (VIS) prior to investigation. Symptoms volunteered by the patient were correlated with formal scoring systems to verify accuracy of symptom reporting and to study the co-existence of FI and RED. Results: One hundred and sixty five women [median age 34 (range 19–55)] were included. Median parity was 2 [range 1–8]. Fourteen women (9.7%) had a 4th degree tear and 68 women (41%) a 3rd degree tear [106 (64%) occurring from the first vaginal delivery]. Three women requiring de-functioning stoma were excluded from further analysis. FI was volunteered in 87 women (54%), [59 urge FI (36%), 57 passive FI (35%) and 28 mixed FI (17%)]. Ninety women (56%) volunteered symptoms of RED. Co-existent symptoms of RED and FI were present in 58 women (36%). VIS and CCCS were available for 79 patients. Median VIS was 8 (IQR 4–13), and was significantly higher in those reporting FI symptoms [median score 11 (IQR 8–15)] than those not [median score 4 (IQR 0–8)] (p < 0.0001 Mann Whitney U Test). Median CCCS was 8 (IQR 4–14), which was significantly higher in those reporting RED symptoms [median score 13 (IQR 11–17)] than those not [median score 5 (IQR 3–8)] (p < 0.0001 Mann Whitney U Test). Fifty four patients (68%) had significant FI based on VIS (score > 5) and 39 patients (49%) had significant RED based on CCCS (score > 8). Thirty patients (38%) had scores compatible with significant co-existent FI and RED. Conclusion: These results demonstrate symptoms of FI and RED often co-exist following obstetric injury regardless of method used to ascertain symptoms. A multi-modality treatment approach addressing overlapping pathophysiologies should be considered in these patients. Disclosure of Interest: None Declared